2019
DOI: 10.1038/s41598-019-43407-z
|View full text |Cite|
|
Sign up to set email alerts
|

Comprehensive Analysis of Animal Models of Cardiovascular Disease using Multiscale X-Ray Phase Contrast Tomography

Abstract: Cardiovascular diseases (CVDs) affect the myocardium and vasculature, inducing remodelling of the heart from cellular to whole organ level. To assess their impact at micro and macroscopic level, multi-resolution imaging techniques that provide high quality images without sample alteration and in 3D are necessary: requirements not fulfilled by most of current methods. In this paper, we take advantage of the non-destructive time-efficient 3D multiscale capabilities of synchrotron Propagation-based X-Ray Phase Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 45 publications
0
48
0
Order By: Relevance
“…21 In recent years, X-ray computed tomography using synchrotron radiation has emerged and has been validated for imaging of different cardiac pathologies by assessing native intact animal heart models, as well as ex vivo human fetal hearts, and transmural samples of adult human hearts, both normal and disease-affected (such as fetuses with congenital heart disease). 6,7,8,9,10,11,12,13,14,15,16 For example, Gonzalez-Tendero et al illustrated that PB X-PCI can quantify cardiac structures and tissue with enough details to reveal micro ber and vascular structure throughout whole rodent and rabbit fetal hearts, focusing on remodeling associated with intrauterine growth restriction. 6,15 They showed that the great advantage of PB X-PCI, as compared to micro-computed tomography (micro-CT), is that it provides a better contrast between soft cardiac tissues than classical X-ray absorption imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In recent years, X-ray computed tomography using synchrotron radiation has emerged and has been validated for imaging of different cardiac pathologies by assessing native intact animal heart models, as well as ex vivo human fetal hearts, and transmural samples of adult human hearts, both normal and disease-affected (such as fetuses with congenital heart disease). 6,7,8,9,10,11,12,13,14,15,16 For example, Gonzalez-Tendero et al illustrated that PB X-PCI can quantify cardiac structures and tissue with enough details to reveal micro ber and vascular structure throughout whole rodent and rabbit fetal hearts, focusing on remodeling associated with intrauterine growth restriction. 6,15 They showed that the great advantage of PB X-PCI, as compared to micro-computed tomography (micro-CT), is that it provides a better contrast between soft cardiac tissues than classical X-ray absorption imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Edge 4.2 CMOS detector (PCO AG, Kelheim, Germany). The resulting dataset is used for navigation of regions of interest to be imaged with a HR setup (at 0.65 µm effective pixel size, sample-detector distance of 20cm, with a LuAG:Ce 20 µm scintillator (Crytur, Czech Republic) and a PCO.Edge 5.5 CMOS detector (PCO AG, Kelheim, Germany)), and for o ine assessment of whole organ remodeling, cardiomyocytes orientation analysis, and vasculature visualization 7. …”
mentioning
confidence: 99%
“…Approaches of 3D multiscale phase-contrast X-ray tomography with synchrotron radiation have been realized before, e.g. by Dejea et al (2019) at the TOMCAT beamline with an effective pixel size of 5.8 mm for low and 0.65 mm for highresolution tomograms, respectively. Massimi et al (2019) used two different beamline endstations for scans with a pixel size of 1.62 mm at TOMCAT and 50 nm at ID16A-ESRF.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of propagation-based X-ray phase-contrast tomography for three-dimensional (3D) virtual histology has been pointed out by a number of recent studies (Saccomano et al, 2018;Tö pperwien et al, 2018;Khimchenko et al, 2016;Albers et al, 2018;Dejea et al, 2019;Ding et al, 2019;De Clercq et al, 2019;Strotton et al, 2018;Mei et al, 2020). Notably, 3D virtual histology by phase-contrast X-ray tomography is able to extend classical histological two-dimensional (2D) approaches, which are based on thin sections and light microscopy, into a full 3D visualization with isotropic resolution and without destructive slicing of the specimen.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to conventional histology based on thin sections, propagation-based x-ray phase-contrast tomography (PC-CT) offers a full 3D visualization with isotropic resolution and without destructive slicing of the specimen ( Ding et al, 2019 ; Dejea et al, 2019 ; Saccomano et al, 2018 ; Töpperwien et al, 2018 ; Khimchenko et al, 2016 ). The interaction of x-rays with the object is described by the continuous complex-valued index of refraction .…”
Section: Introductionmentioning
confidence: 99%